2018
DOI: 10.1002/pds.4655
|View full text |Cite
|
Sign up to set email alerts
|

Blood eosinophilia, use of inhaled corticosteroids, and risk of COPD exacerbations and mortality

Abstract: PurposeIt remains unclear whether eosinophilia is useful for in guiding inhaled corticosteroid (ICS) therapy in chronic obstructive pulmonary disease (COPD) patients. The goal of this study is to evaluate the risk of acute exacerbations, COPD‐related hospitalisations/accident and emergency visits, and all‐cause mortality with various levels of eosinophil counts among COPD patients using ICS.MethodsA cohort study was conducted using the UK Clinical Practice Research Datalink. Patients were aged 40+ and had COPD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…28 Recently, Oshagbemi and coworkers reported retrospective observational real-world data indicating that ICS reduced mortality in COPD patients with blood eosinophilia. 29 These findings suggest that there might be COPD phenotypes in which ICS can reduce mortality. Heterogeneity of the COPD populations in this and other studies, and the existence of different, today insufficiently understood COPD phenotypes may explain the various results in different studies.…”
Section: Discussionmentioning
confidence: 96%
“…28 Recently, Oshagbemi and coworkers reported retrospective observational real-world data indicating that ICS reduced mortality in COPD patients with blood eosinophilia. 29 These findings suggest that there might be COPD phenotypes in which ICS can reduce mortality. Heterogeneity of the COPD populations in this and other studies, and the existence of different, today insufficiently understood COPD phenotypes may explain the various results in different studies.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, several observational studies among COPD patients using ICS did not find an association between blood eosinophilia and reduced risk of exacerbations [ 83 , 84 ]. The lack of relationship shown in the observational studies suggests that this association may not be present within the real-world COPD population.…”
Section: Existent Type2 Biomarkers In Copdmentioning
confidence: 94%
“…In our previous work using COPD patients from the same data source, we found similar results for moderate-to-severe and severe exacerbations. However, an important difference is the fact that in our previous study only patients with prior history of ICS use were included (29). Analyses of data from the FLAME trial reported that LABA/LAMA combination was superior to LABA/ICS combination in exacerbation reduction for relative or absolute blood eosinophil threshold (2%, !2%, 3%, <5% and <150 cells/ml subgroups), and at no threshold was LABA/ICS superior to LABA/LAMA (8).…”
Section: Discussionmentioning
confidence: 94%